New Glutamine-Containing Azaphilone Alkaloids from Deep-Sea-Derived Fungus Chaetomium globosum HDN151398 - Chunxiao Sun (Marine Drugs, 2019)
Three new azaphilone alkaloids containing glutamine residues, namely N-glutarylchaetoviridins A−C (1−3), together with two related compounds (4 and 5) were isolated from the extract of Chaetomium globosum HDN151398, a fungus isolated from a deep-sea sediment sample collected in South China Sea. Their structures were elucidated on the basis of extensive 1D and 2D NMR as well as HRESIMS spectroscopic data and chemical analysis. N-glutarylchaetoviridins A−C (1−3) represent the first class of chaetoviridins characterized by embedded glutamate residues. Amino acids incubation experiments produced five azaphilone laden different amino acids residues (6−10) which indicated that this method can enhanced the structural diversity of this strain by culturing with amino acids. Cytotoxicity of the isolated compounds were evaluated against a panel of human cancer cell lines.